2012
DOI: 10.1021/ct300117j
|View full text |Cite
|
Sign up to set email alerts
|

Druggability Assessment of Allosteric Proteins by Dynamics Simulations in the Presence of Probe Molecules

Abstract: Druggability assessment of a target protein has emerged in recent years as an important concept in hit-to-lead optimization. A reliable and physically relevant measure of druggability would allow informed decisions on the risk of investing in a particular target. Here, we define “druggability” as a quantitative estimate of binding sites and affinities for a potential drug acting on a specific protein target. In the present study, we describe a new methodology that successfully predicts the druggability and max… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
186
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(192 citation statements)
references
References 83 publications
6
186
0
Order By: Relevance
“…Currently, the only approaches to cryptic site discovery are exhaustive site-directed small-molecule tethering by experiment (2022), long time-scale molecular dynamics simulations by computation (6, 8, 23, 24), flexible docking (25, 26), and computational tools for identification of small-molecule binding hot spots (10, 2730). All of these approaches are time-consuming, expensive, and/or not always successful.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the only approaches to cryptic site discovery are exhaustive site-directed small-molecule tethering by experiment (2022), long time-scale molecular dynamics simulations by computation (6, 8, 23, 24), flexible docking (25, 26), and computational tools for identification of small-molecule binding hot spots (10, 2730). All of these approaches are time-consuming, expensive, and/or not always successful.…”
Section: Introductionmentioning
confidence: 99%
“…‘Hot spots’ having all 16 probes bound are identified as druggable [19]. Bakan et al used molecular dynamics simulations for solvent mapping with a different set of small fragment probes and found that the probes bind known allosteric sites during the simulation [20]. Brown and Hajduk earlier showed that molecular dynamics simulations can capture pocket dynamics that result in a more druggable binding pocket in Bcl-xl, while preserving much of the known binding site rigidity of Akt-PH and FKBP [21].…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, it is likely possible to find all known druggable sites using molecular dynamics, including some that are undetectable by our method. However, separating the signal from the noise is challenging [20], [21] since there is a tendency for many pocket openings to be observed. To be clear, our approach does not reveal any new pockets that do not already exist within the rigid structure.…”
Section: Resultsmentioning
confidence: 99%
“…ProDy [147] is a Python toolkit for analyzing proteins and includes facilities for trajectory analysis and druggability predictions using simulations of molecular probes [152]. …”
Section: Ligand Dynamics and Free Energy Calculationsmentioning
confidence: 99%